Opportunities for Climate Finance in the Livestock Sector : Removing Obstacles and Realizing Potential - World Bank (World Bank, Washington, DC, 2021)
Important mitigation outcomes and other co-benefits could be at reach if rural communities and policy makers in low- and middle-income economies overcame the obstacle of access to finance in the livestock sector. The traditional sources of financing have long been difficult to access for livestock smallholders who often do not hold collateral except for their animals and have little experience of working with financial institutions. Traditional lenders see the livestock sector as overly risky, with little potential for significant profits, leaving them largely uninterested. Expanding financial inclusion would improve livelihoods, increase resilience, and help reduce GHG emissions. Innovative approaches to financing for the livestock sector are needed. In a sector that plays an essential economic role for some 60% of rural households, including 1.7 billion people and contributes up to half of agricultural GDP, reducing carbon emissions while maintaining livelihoods and reducing poverty is essential. This report identifies investment opportunities for increasing climate finance in the sector and drive its sustainable transformation.